Effects of assisted outpatient treatment and health care services on psychotic symptoms. (February 2017) - Schneeberger, Andres R.; Huber, Christian G.; Lang, Undine E.; Muenzenmaier, Kristina H.; Castille, Dorothy; Jaeger, Matthias; Seixas, Azizi; Sowislo, Julia; Link, Bruce G.
Abstract: Rationale: An ongoing debate concerns acceptability, benefits, and shortcomings of coercive treatment such as assisted outpatient treatment (AOT). The hypothesis that involuntary commitment to outpatient treatment may lead to a better clinical outcome for a subgroup of persons with severe mental illness (SMI) is controversial. Nonetheless, positive effects of AOT may be mediated by an increased availability of healthcare resources or increased service use. Objective: The purpose of the present study is to evaluate the course of delusions, hallucinations, and negative symptoms among patients with SMI receiving AOT compared to patients receiving non-compulsory treatment (NCT). Moreover, we assessed if the effects of AOT on psychotic symptoms were mediated by increased healthcare service use. Methods: This study used a quasi-experimental design to examine the effect of AOT and the use of healthcare services on psychotic symptoms. In total, 76 (41.3%) participants with SMI received AOT, and 108 (58.7%) received NCT. The participants were interviewed at baseline every 3 months up to 1 year. Propensity score matching was used to control for group differences. Results: In the basic model, AOT was associated with lower severity of psychotic symptoms over all follow-up points. In the model including healthcare service use, the frequency of case manager visits predicted a reduction in severity of all psychotic symptoms. The frequency of visits to the outpatient clinics, frequency of emergency room, and psychiatrist visits were independently associated with lower levels of delusional symptoms. Psychiatrist visits were related to a decrease in negative symptoms. Conclusion: Results indicate that the treatment benefits of AOT are enhanced with the increased use of mental healthcare services, suggesting that the positive effect of AOT on psychotic symptoms is related to the availability of mental healthcare service use. Coercive outpatient treatment might be more effective through greater use of intensive services. Highlights: Patients in assisted outpatient treatment (AOT) exhibit better functioning. Psychiatrist visits lead to reduced delusions and negative symptoms. Outpatient clinics mediate the useful reductions of delusions and negative symptoms. Contacts with a case manager are linked with lessened overall psychotic symptoms. Positive effects of AOT are not primarily related to coercion.